Selective Crystallization of Silicoalumophosphate Sapo-11 With A Micromesoporous Structure - Khayrullina, Zulfiya; Ahmed, Kanaan R.; Kambarova, Samara; Agliullin, Marat (Science Journal of University of Zakho, 2021)
ABSTRACT:The authors have proposed a method for the selective crystallization of a SAPO-11 silicoaluminophosphate molecular sieve with a micro-mesoporous structure. It has been shown that crystallization of a silicoaluminophosphate gel, in the preparation of which its isopropoxide is used as a source of aluminum, makes it possible to obtain a SAPO-11 molecular sieve with a specific surface area of ​​~ 207 m2 / g, a volume of micro- and mesopores of ~ 0.08 and 0.09 cm3 / g. , respectively. Using scanning electron microscopy, it was demonstrated that the crystals of the material are pseudospherical particles ~ 8-10 microns in size, consisting of aggregates of nanocrystals ~ 100-200 nm in size.
Keywords: Mesoporous Zeolites; Heterogeneous Catalysis; Zeolites; SAPO-N Silicoaluminophosphates; Hydroisomerization of Higher Paraffins